Produktivitas Pekerja Pada Pekerjaan Kolom Lantai 1 dan 2 Ruko Romance Sidoarjo Dengan Metode Pengamatan Langsung - AL KINDI, MUHAMMAD FIZHOM (Universitas Negeri Surabaya, 2023)
Construction projects are one of the activities where labor productivity affects work efficiency. Labor productivity is a value that cannot be known directly, this value can be known after going through the calculation process. Productivity calculations for column structure work on floors 1 and 2 for the construction of the Romance shophouse project are carried out to determine the value of the productivity of the workers. The method of calculating worker productivity that will be used to measure each activity is the direct observation method. By observing and seeing the activities of these workers directly during the activities carried out. The results of observations in the field and the results of calculations that have been carried out, the average value of worker productivity for the columns of the 1st and 2nd floors was obtained at 189.65 Kg/OH and 197.30 Kg/OH, the formwork for columns for the 1st and 2nd floors was obtained at 14.77 m2 /OH and 14.25 m2/OH, and the casting of the 1st and 2nd floor columns was obtained at 1.01 m3/OH and 0.22 m3/OH.